Perception Of Environment Among The School Students In Dindigul District - Srinidhi S, Pugalenthi Thangavelu (South Eastern European Journal of Public Health, 2025)
The past and present situation creates the awareness and urge that environmental education is more needed for young minds to have future perspectives for sustainable development in the nation. But in recent years, the citizens of the country have seen an increase in environmental issues particularly climate change with pollution and biodiversity loss. Therefore, it is urgent to create knowledge of the environment among the students and positive behavioral change in the young minds, children. Hence, the children must be taught the importance of maintaining ecological balance and protecting natural resources not only as a supplement subject but also by prioritizing it as life science because they will be the planet's future. Educators and institutions must have an understanding and be clear about how children view environmental issues. Hence this paper concentrates on the perception of the environment among the school students with the following objectives. The research study collected data from 810 schoolchildren. Multistage sampling method is used to find out the determinants of knowledge, attitude and applications of environmental aspects, binary logistic regression analysis was used.